SHOOTING RANGE IMPROVEMENT BY MONITORING THE DISCRIMINATING FACTORS OF THE JUNIOR BIATHLETES - B.I. PELIN1; D. BONDOC-IONESCU (Editura Universitatii Transilvania din Brasov, 2020)
The purpose of the research is to identify biomechanical predictors that distinguish between high and low score athletes in biathlon shooting and to determine the relationships among these variables in field testing. Ten biathletes (3 female, 7 male) from CSS Dinamo Râșnov each fired 3 clips of 5 shots in prone and standing shooting positions without physical load, followed by 2 respective series in both disciplines during a simulated 12.5-km pursuit race on roller skis. Referring to the current results, athletes are recommended to focus on vertical rifle sway in prone position and on body sway across the shooting line during standing shooting when fatigued.